Judaism, history, and the environment: climate change and natural disasters - Bell, Dean Phillip (Bloomsbury Academic, 2025)
"Engaging creatively with Jewish sources and history, this book offers new ways of addressing the issues of the Anthropocene and natural disasters. Rather than seeing religion as a stumbling block or cause of environmental degradation, historical examples are instead bought into conversation with classical Jewish texts and contemporary Jewish thought. Case studies include earthquakes of Georgian England, floods of 18th century Germany, and natural disasters experienced by Jews in the Ottoman Empire. Presented is an important argument showing how new engagement with Jewish history and thought may help us to grapple with the environmental challenges of today and the future"--